Removal of Cr(VI) from aqueous solution by biochar derived from rice husk - Mohadi, Risfidian; Palapa, Neza Rahayu; Taher, Tarmizi; Siregar, Patimah Mega Syah Bahar Nur; Normah; Juleanti, Novie; Wijaya, Alfan; Lesbani, Aldes (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
In this work, biochar produced from Indonesian rice husks. Then used as adsorbent of Cr(VI) in aqueous solution. The XRD pattern of biochar showed the characterization pattern at 23º (002) reflection, appearance of silicate oxide, and the carbon vibrations. The surface area and SEM morphologies confirmed that after pyrolysis treatment the surface of rice husk has changed. The surface area of biochar increased after thermal treatment. The adsorption study of Cr(VI) by biochar demonstrate 2nd-order reaction, and Langmuir isotherm models. The maximum adsorption capacity of biochar derived rice husk to adsorb Cr(VI) is 161.290 mg/g, and biochar showed the good potential as reuseable adsorbent to remove heavy metal in aqueous solution.